Risk factors for postoperative medical morbidity and 3-month mortality in elderly patients with hip fracture following hip arthroplasty during COVID-19 pandemic - Huarui Shen; Rui He; Peng Zhang; Yue He; Yingqi Liu; Guoyou Wang; Ting Li (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background The purpose of the current study was to investigate the incidence of postoperative medical complications and 3-month mortality in patients  ≥ 70 years old with hip fracture following hip arthroplasty (HA) and independent risk factors associated with postoperative medical complications and 3-month mortality during the Coronavirus Disease 2019 (COVID-19) pandemic. Methods A multicenter retrospective study was conducted, patients  ≥ 70 years old with HA for hip fracture under general anesthesia were included during COVID-19 and before COVID-19 pandemic. The outcome was defined as postoperative medical complications and 3-month mortality. The baseline characteristics and risk factors were collected, multivariable logistic regression was used to identify independent risk factors for postoperative medical complications and 3-month mortality. Results A total of 1096 patients were included during COVID-19 pandemic and 1149 were included before COVID-19 pandemic in the study. Patients  ≥ 70 years with hip fracture for HA had longer fracture to operation duration (7.10 ± 3.52 vs. 5.31 ± 1.29, P < 0.001), and the incidence of postoperative medical complications (21.90% vs. 12.53%, P < 0.001) and 3-month mortality (5.20% vs. 3.22%, P = 0.025) was higher during COVID-2019 pandemic. Multivariate logistic regression analysis showed that dementia (OR 2.73; 95% CI 1.37–5.44; P = 0.004), chronic obstructive pulmonary disease (COPD) (OR 3.00; 95% CI 1.92–4.71; P < 0.001), longer fracture to operation duration (OR 1.24; 95% CI 1.19–1.30; P < 0.001) were associated with increased risk for postoperative medical complications. COPD (OR 2.10; 95% CI 1.05–4.17; P = 0.035), dementia (OR 3.00; 95% CI 1.11–7.94; P = 0.031), postoperative medical complications (OR 4.99; 95% CI 2.68–9.28; P < 0.001), longer fracture to operation duration (OR 1.11; 95% CI 1.04–1.19; P = 0.002) were associated with increased risk for 3-month mortality. Conclusions In conclusion, we found that postoperative medical morbidity and 3-month mortality in patients with hip fracture underwent HA were 21.90% and 5.20%, respectively, during the COVID-19. COPD, dementia and longer fracture to operation duration were associated with negative outcome in patients with hip fracture underwent HA during the COVID-19.